Theory of Planned Behavior on Factors Affecting Tetanus Toksoid Immunization Uptake Among Pregnant Women in Boyolali, Central Java - Yumafita, Tiara; Rahardjo, Setyo Sri; Adriani, Rita Benya (Journal of Maternal and Child Health, 2019)
Background: Tetanus is an infectious disease caused by Clostridium tetani bacteria. TT immunization in pregnant women can prevent neonatal deaths. Maternal and Neonatal Tetanus (MNT) has been among the most common life-threatening consequences of unclean deliveries and umbilical cord care practices, and are indicators of inequity in access to immunization and other maternal, newborn, and child health services. The neonatal mortality rate was still high in Boyolali Regency, Central Java. The purpose of this study was to determine the factors of TT immunization uptake among pregnant women in Boyolali, Central Java, using Theory of Planned Behavior. Subjects And Method: This was a cross-sectional study conducted in Boyolali, Central Java, from November to December 2018. A sample of 200 pregnant women from 25 community health centers was selected by simple random sampling and positioned at level 2 in a multilevel model analysis. Eight pregnant women were selected at random from each community health center. The dependent variable was TT immunization uptake. The independent variables were knowledge, education, the influence of midwife private practice, parity, income, intention, attitude, perceived behavior control, and social norm. The data on immunization uptake was obtained from the medical record. The other data were collected by questionnaire. The data were analyzed by multilevel multiple logistic regression analysis. Results: The use of TT immunization increased with better maternal knowledge (b= 1.47; 95% CI= 0.02 to 2.92; p= 0.047), high maternal education (b = 2.19; 95% CI = 0.64 to 3.75; p= 0.006), influence of midwife private practice (b= 2.07; 95% CI= 0.41 to 3.72; p= 0.014), parity ?2 (b= 1.81; 95% CI = 0.13 to 3.5; p= 0.034), income ?minimum regional wage (b= 1.95; 95% CI= 0.39 to 3.50; p= 0.014), strong intention (b = 1.73; 95% CI = 0.11 to 3.34; p= 0.035), positive attitude (b= 2.11; 95% CI = 0.17 to 4.05; p= 0.033), strong perceived behavior control (b= 3.84; 95% CI = 1.47 to 6.20; p <0.001), supportive social norm (b= 2.26; 95% CI= 0.29 to 4.23; p= 0.024). Community health center had a contextual effect on TT immunization uptake with ICC= 35.86%. Conclusion: The use of TT immunization increased with better maternal knowledge, high maternal education, the influence of midwife private practice, parity ?2, income ?minimum regional wage, strong intention, positive attitude, strong perceived behavior control, supportive social norm. The community health center has a contextual effect on TT immunization uptake. Keywords: TT immunization, knowledge, education, midwife private practice, parity, income, intention, attitude, perceived behavior control, social norm, pregnant women Correspondence: